INVENTARISASI DAN ANALISIS TANAMAN UNTUK PENGAMANAN BANTARAN SUNGAI DI SEKITAR DAERAH ALIRAN SUNGAI TUKAD PAKERISAN - Budiasa, I Made; Widnyana, I Ketut; Arnawa, I Ketut; Prasetia, I Nyoman Budi (Jurnal Alam Lestari, 2021)
Tukad Pakerisan River is one of the rivers that crosses 4 (four) sub-districts in the 34.5 km long Gianyar Regency and is one of the world heritage sites where its existence is now threatened by settlements around the river banks. The purpose of this study is to carry out an inventory of plant species that have a function as a safeguard of riverbanks from upstream to downstream and to analyze the diversity of protective plants in the Pakerisan riverbank. The method used is to conduct a field survey to identify the types of plants species that are able to protect the riverbanks and to analyze the indexes of important values ​​and plant diversity. The results showed several species of plants that are able to protect the riverbank: 1) in the upstream section, there are palm sugar, bamboo, waru, stretched, banyan, albasia, and coconut tree, 2) in the middle section, there are bamboo, sugar palm, jackfruit, coconut, durian, banyan, albasia, and mahogany., and 3)in the downstream section, there are ketapang, coconut, jackfruit, bamboo, breadfruit, mahogany, noni, waru, banyan and lamtoro. Based on the results of the important value index analysis, the largest value index in the upstream is owned by bamboo tree (1.614%), in the middle part is owned by coconut tree (0.793%), and in the downstream part is owned by coconut tree (1.016%). The level of diversity of plants that have a function as a protector of river banks is increasing from the upstream to the downstream. The greatest level of diversity is in the downstream areas.